Biopolitics and Boundary Work in South Africa's Sutherlandia Clinical Trial. Issue 7 (3rd October 2017) - Morris, Christopher
ABSTRACT: Between 2008 and 2011, South African and American investigators carried out a randomized controlled trial to assess the safety and efficacy of an African traditional medicine in South Africans who were HIV-seropositive but asymptomatic. The medicine was derived from Sutherlandia frutescens, a plant endemic to and widely used to stimulate immune function by people across southern Africa. In this article, I report on the cross-cultural challenges generated by trial investigators' transformation of Sutherlandia into a clinical trial substance and a potential "treatment gap" therapy for persons with HIV. While Sutherlandia is in many respects an unusual addition to evidence-based medicine, it is also familiar in this context—especially in the manner the therapy was biopolitically imagined by trial investigators, and in terms of the indeterminacy the therapy produced.